Persepsi Siswa Terhadap Quizizz Terintegrasi Google Classroom untuk Meningkatkan Minat Belajar Bahasa Indonesia - Abidin, Zainal; Rochmiyati, Siti (WASIS : Jurnal Ilmiah Pendidikan, 2024)
The focus of this research is the implementation of Quizizz integrated with Google Classroom (GCR) as an innovative solution to enhance students' learning interest. The main objective is to explore how the application of this technology influences students' perceptions of the Indonesian language subject and how it motivates them to learn better. By detailing students' perceptions and the impact of technology, this study provides profound insights into the potential of technology-based learning in creating engaging and effective learning experiences. The research method employed is classroom action research conducted at SD Negeri Sumber 2, involving 10 fifth-grade students. Data were collected through questionnaires, observations, and interviews. The results indicate that learning through Quizizz integrated with GCR has a positive impact on students' learning interest, with high levels of enjoyment, interest, and attention reported by the students. Although students' engagement in online learning shows variations, the use of this technology significantly contributes to improving students' learning interest. The implications of this research suggest that e-learning approaches through platforms like Quizizz integrated with GCR have substantial potential to enhance students' learning interest in the context of digitally-transformed education.